1985
DOI: 10.1128/jvi.53.2.679-683.1985
|View full text |Cite
|
Sign up to set email alerts
|

Virions and intracellular nucleocapsids produced during mixed heterotypic influenza infection of MDCK cells

Abstract: Phenotypically mixed virus yields, obtained by coinfection of MDCK cells with influenza A/WSN/33 and B/Lee/40 viruses, contained both A/WSN/33 and B/Lee/40 NP proteins, as revealed by polyacrylamide gel electrophoresis of the purified '4C-amino acids-labeled virus. Virions were lysed with 0.6 M KCI-Triton X-100 buffer, and nucleocapsids were immunoprecipitated with antibodies against NP protein of influenza A virus. Polyacrylamide gel electrophoresis of the immunoprecipitate revealed NP protein of AIWSN/33 but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It is possible that the N-terminal extension of type B virus NP has a role in the specific incorporation of vRNPs into influenza B virus particles. It has been reported that, while type A and B virus NPs may exist in the same RNP complex in vivo, these phenotypically mixed forms are not incorporated into virions (33). Since the NPs of type A and B viruses differ most at their N termini, the N-terminal extension may be involved in the selection of RNPs containing only type B virus NP.…”
Section: N-terminal Deletions In Influenza B Virus Np Do Not Affect Tmentioning
confidence: 99%
“…It is possible that the N-terminal extension of type B virus NP has a role in the specific incorporation of vRNPs into influenza B virus particles. It has been reported that, while type A and B virus NPs may exist in the same RNP complex in vivo, these phenotypically mixed forms are not incorporated into virions (33). Since the NPs of type A and B viruses differ most at their N termini, the N-terminal extension may be involved in the selection of RNPs containing only type B virus NP.…”
Section: N-terminal Deletions In Influenza B Virus Np Do Not Affect Tmentioning
confidence: 99%
“…In contrast, the cytoplasmic tails of the other two virion envelope proteins, haemagglutinin (HA) and neuraminidase (NA), can be deleted both individually or simultaneously without loss of virus viability (Garcia-Sastre and Palese, 1995;Jin et al, 1997). Incorporation of HA into influenza particles is not a type-specific event because influenza A virus HA proteins are incorporated into influenza B virus particles after double infection of cells (Sklyanskaya et al, 1985). Whether the NA proteins also show phenotypic mixing is not known, although it is noteworthy that an influenza A virus has been recovered in which the sequence of the cytoplasmic tail of NA was exchanged for that of an influenza B virus NA protein (Bilsel et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the RNA length, each RNP segment contains from 30 to 100 molecules of the major nucleocapsid protein (NP) (19,45) and several molecules of three high-molecular-mass (ϳ90 kDa) polymerase proteins: PB1, PB2, and PA (10,40,50). The viral RNP structures mediate transcription and replication of the viral genome (13,25,30) and participate in the morphogenesis and assembly process of virus particles (37,54,60) in infected cells. NP plays significant roles in these events by regulating intracellular transport of viral RNPs (5,35,55) and metabolic processes of transcription and replication (6,9,28,53).…”
mentioning
confidence: 99%